Factors influencing aggressive behavior as perceived by university students - Ateya Megahed Ibrahim; Donia Elsaid Fathi Zaghamir; Mutaz F. Alradaydeh; Mohamed Gamal Elsehrawy (Elsevier, 2024)
Background: The mainstay of producing highly qualified people in a nation is post-secondary education. A lot of pressure is placed on students to succeed. Aim: Explore the predictors of aggression within university students in Jordan. Methods: The study employed a correlation design with a self-administered questionnaire distributed among Jordan University students using convenience sampling. Inclusion criteria encompassed currently enrolled students with adequate language proficiency and cognitive abilities, while exclusion criteria included absent or non-participating students. Prior to data collection, participants were provided with an invitation letter emphasizing privacy protection. Distribution occurred during academic classes, resulting in a 93 % response rate from 1,000 distributed questionnaires. After data screening, 925 questionnaires were deemed suitable for analysis. Ethical approval was obtained from the University of Jordan's institutional review board (IRB), with participants assured of voluntary participation and confidentiality. These measures uphold rigorous research standards and ethical conduct. Results: Depression, life satisfaction and spiritual well-being were significant predictors of aggression. life satisfaction and Spiritual well-being was inversely related to aggression, while depression was positively related to aggression. Higher levels of hostility were more frequently reported by male university students than female university students. Conclusion: Providing contentious assessment for psychosocial and spiritual well-being are important way to manage aggression among university students. Recommendations: The current study recommends elevating the function of social workers, mental health nurses, and psychological counselors in order to give periodic assessment, and to screen the psychosocial health indicators of aggression such as depression, a lack of spiritual health and a lack of life satisfaction.